2003
DOI: 10.1159/000071467
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Hypothalamic-Pituitary-Adrenal Disregulation during the Third Trimester Influences Human Fetal Responses

Abstract: Maternal peptides from the hypothalamic-pituitary-adrenal (HPA) axis rise during human pregnancy. The effects of circulating maternal adrenocorticotropin (ACTH) and β-endorphin (BE) on human fetal behavior was determined in 135 women during their 32nd week of gestation. Fetal behavior was measured by assessing heart rate habituation to a series of repeated vibroacoustic stimuli. Individual differences in habituation were determined by computing the number of consecutive responses above the standard deviation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 104 publications
2
50
0
Order By: Relevance
“…With measures of FHR we discovered that fetuses of women with elevated pCRH during the third trimester were less responsive to the presence of a novel stimulus [41]. In a subsequent study, we reported that FHR habituation was delayed when fetuses were exposed to over-expression of maternal endogenous opiates [42]. To evaluate programming influences on the fetus, we assessed the consequences of gestational stress during the early second trimester on fetal behavior in the early third trimester.…”
Section: Gestational Stress Influences Human Fetal Behaviormentioning
confidence: 99%
“…With measures of FHR we discovered that fetuses of women with elevated pCRH during the third trimester were less responsive to the presence of a novel stimulus [41]. In a subsequent study, we reported that FHR habituation was delayed when fetuses were exposed to over-expression of maternal endogenous opiates [42]. To evaluate programming influences on the fetus, we assessed the consequences of gestational stress during the early second trimester on fetal behavior in the early third trimester.…”
Section: Gestational Stress Influences Human Fetal Behaviormentioning
confidence: 99%
“…One of the major placental stress signals in pregnant primates is the peptide corticotropin-releasing hormone (CRH). This peptide plays a key role in the maturation of the fetal hypothalamic-pituitary-adrenal-axis (HPA-axis) and other systems, and coordinates events that underlie both fetal growth and maturation and the time of onset of parturition (Hobel, Dunkel-Schetter, Roesch, Castro, & Arora, 1999;Sandman et al, 2006;Sandman et al, 2003;Sandman et al, 1999b;Wadhwa et al, 2004;Wadhwa, Porto, Garite, Chicz-DeMet, & Sandman, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme 11β-hydroxysteroid dehydrogenase-2 (11β-HSD-2) has been isolated in the human placenta and likely accounts for the relatively low transfer of maternal cortisol to the fetus by converting cortisol to its inactive form cortisone (Benediktsson et al, 1997;Bernal, Flint, Anderson, & Turnbull, 1980). 11β-HSD-2 shows steady increases throughout gestation until the last few weeks of gestation when decreases in 11β-HSD-2 are observed (Lopez Bernal, Anderson, & Turnbull, 1982;Murphy & Clifton, 2003;Sandman et al, 2003;Schoof et al, 2001;Shams et al, 1998). Although, 11β-HSD-2 provides protection for the fetus from maternal cortisol, it does not provide complete protection; thus, some maternal cortisol continues to reach the fetus.…”
Section: Introductionmentioning
confidence: 99%
“…The association between maternal plasma concentrations of CRH and preterm labor/delivery has been examined in many published studies (Markovic et al, 2007). During pregnancy, maternal stress threatens the fetal nervous system (Coe et al, 2003;Insel et al, 1990;Poland et al, 1999;Sanchez et al, 1993;Sandman et al, 2003;Sandman et al, 1999a;Sandman et al, 1999b;Weinstock, 1996) and shortens the length of gestation (Campbell et al, 1987;McLean et al, 1995;Wadhwa et al, 2004;Wadhwa et al, 1998;Wadhwa et al, 1993;Warren et al, 1992;Wolfe et al, 1988). The general findings are that plasma CRH concentrations of women in preterm labor are significantly higher than those of gestationalage matched controls and the rate of change of CRH over gestation is accelerated in women destined to deliver early.…”
Section: Endocrine Riskmentioning
confidence: 99%
“…We discovered that fetuses of women with elevated pCRH during the third trimester were less responsive to the presence of a novel stimulus (Sandman et al, 1999b). In a subsequent study we reported that fetal heart rate habituation was delayed when fetuses were exposed to over-expression of maternal endogenous BE (Sandman et al, 2003). To evaluate programming influences on the fetus, we assessed the consequences of gestational stress during the early second trimester on fetal behavior in the early third trimester.…”
Section: Fetal Behaviormentioning
confidence: 99%